PENGARUH MODEL PEMBELAJARAN DAN EFIKASI DIRI TERHADAP SIKAP ILMIAH SISWA SMA PEMINATAN MIPA - Fajar Adinugraha (Jurnal Pro-Life, 2017)
The research objective is to determine the effect of learning model on scientific attitudes of students, self efficacy towards the scientific attitudes, and the interaction of the learning models and self efficacy towards scientific attitudes. The research method is experimental method. The analyzed data consist of self efficacy instrument test and scientific attitude instrument tests with their validity and reliability assessment. Data were taken by means of two way anova test. The result show that: 1) There is a significant effect of learning model towards student's scientific attitude. 2) There is a significant effect of self efficacy towards students' scientific attitude. 3) There is an interaction effect that is not significant to thelearning model and self efficacy towards students' scientific attitude. Keywords: learning model, self efficacy, scientific attitudes